Localism in Practice: Investigating Citizen Participation and Good Governance in Local Government Standards of Conduct. - Lawton, Alan; Macaulay, Michael (Public Administration Review, 2014)
This article examines how, against a background of localism endorsed by the 2010 coalition government in the United Kingdom, a key component of local integrity and governance was fundamentally altered. The Localism Act 2011 abolished the English local integrity framework, which relied on the participation of local citizens in the policy making and implementation of local government standards of conduct. The article utilizes Henrik Bang's concepts of 'expert citizen' and 'everyday maker' to explore citizen participation in local standards committees. Using a case study approach, the article demonstrates how standards committees shaped processes and practices in the local governance of integrity. The authors argue that standards committees were crucial in promoting local participation and enhancing good governance.